P323 Successful validation of the quantum blue quantitative rapid test to monitor C-reactive protein in capillary blood of patients suffering from chronic inflammatory diseases. (15th January 2020) - Takacs, M; Hellige, A; Schuster, T; Schleifenbaum, S; Föll, D; Weber, J M
Abstract: Background: Only few biomarkers are useful for the therapy monitoring of patients suffering from inflammatory diseases, like inflammatory bowel disease (IBD) or rheumatoid arthritis (RA). Next to calprotectin C-Reactive Protein (CRP) is the best described and usually measured in the central laboratory. However, most patients are regularly checked at GP's offices or small ambulatories. These sites need fast results with simple technology to react immediately. Our quantitative CRP rapid test based on lateral flow technology combined with a cost-effective reader fulfils all these criteria. It can be used with serum and whole blood. Here, we report the validation of the Quantum Blue ® hsCRP in capillary blood and show first clinical applications of this new test. Methods: The sandwich-type lateral flow test employing anti-CRP antibody-coated gold nanoparticles was calibrated with the ERM-DA474 CRP reference material. Fingerprick blood was collected and diluted 1:10 with a dedicated capillary blood preparation set and then applied onto the test cassette. After a 15-min incubation, the readout was performed with the Quantum Blue ® Reader resulting in a quantitative measuring range of 1 to 20 mg/l. 122 capillary blood/serum pairs were collected to compare this rapid hsCRP test with the fully automated serum CRPL3 (PETIA) test on Roche cobas ® c501. Clinical performance data together with concomitant CRP measurements were collated from 20 IBD and 69 RA patients. The resulting capillary blood CRP values including those from 28 healthy subjects were used to establish preliminary clinical cut-off values. Results: 56 capillary blood/serum sample pairs with values within the measuring range of both the hsCRP and the CRPL3 PETIA could be elected for a quantitative comparison. The capillary blood values were corrected against a mean haematocrit of 42%. A strong correlation ( R = 0.941) with a minor bias of 6.1% by Bland-Altman plot was observed. Non-parametric analyses of capillary blood CRP levels from 20 IBD and 69 RA patients vs. their disease activity scores (CDAI, Mayo, DAS28, active joints) resulted in an upper reference limit of 5.8 mg/l and a 95%ile reference range from 1.0 to 19.7 mg/l. Patients with moderate (IBD) to severe (IBD, RA) disease activity could be significantly discriminated by capillary blood CRP from those with low activity or remission. Conclusion: The BÜHLMANN Quantum Blue® hsCRP rapid test allows fast and easy detection of CRP in human capillary blood within 15 min in ambulatory settings. The assay shows an excellent absolute correlation to a fully automated serum CRP reference method. A preliminary clinical cut-off of 5.8 mg/l was established in two cohorts of IBD and RA patients to discriminate high from low disease activity.